Língua Espanhola no Enem: análise de itens de 2019 a 2022 na perspectiva dos Letramentos Críticos - Simone dos Santos Franca (2023)
This doctoral thesis aimed to analyze, from the perspective of critical literacy, the Spanish language items of the National High School Exam (Enem) in the applications from 2019 to 2022. The selection of items considered discussions related to power relations, ideology and diversity; items that were directly related to social practices and that presented the terms criticism/criticality. The research questions that underpin this investigation were: a) Do the base texts, statements and alternatives collaborate to critically discuss social practices, power relations and ideology? If so, how? b) Are there aspects of critical literacy in the base texts, statements and alternatives of the Spanish language items of the Enem? The specific objectives of this research are: (i) to discuss the importance of Spanish in the Enem; (ii) to analyze how Spanish language items in the Enem can enable discussions about social practices, power relations and ideologies; (iii) discuss the importance of Enem Spanish items that present a critical perspective of language, according to the assumptions of critical literacies; (iv) discuss the implications of Enem for the teaching and learning of Spanish in high school, from the perspective of critical literacies. This research is situated in the field of Applied Linguistics studies focused on research concerning Spanish teaching and Enem, relating language and society. Thus, the analysis focuses on nine Enem Spanish items based on three elements that integrate each question: the base text, the statement and the alternatives. The thesis defended is that, from the choice of certain texts, it is possible to provoke critical reflections that contribute to the ideal of a linguistic education and that allow the expansion of the social consciousness of individuals so that they reflect and act in their own reality. This is a qualitative research (LANKSHEAR; KNOBEL, 2008), of descriptive-interpretativist nature (MOITA LOPES, 1994). Among the justifications for this investigation are the yearnings arising from my performance as a high school teacher for some years, in which I could see the need for the development of criticality among students, and observe the retroactive effects of Enem in my classes. The experience motivated me to develop this research in the intention that it contributes, in some way, to foster investigations on Spanish language items of Enem. In addition, it is intended that it collaborates with other academic works related to Spanish items and critical literacy theory. Also, that it allows teachers, students, item developers and the community in general to realize the need to propose themes/texts that claim a more critical look at students as citizens and their engagement through language. As a theoretical basis, studies on critical literacy (CERVETTI; PARDALES; DAMICO, 2001; JANKS, 2010, 2012, 2013; MENEZES DE SOUZA, 2011; MONTE MÓR, 2008, 2010, 2011, 2013; STREET, 2014) and Spanish (BAPTISTA, 2007, 2010; BOTELHO, 2021; CASSANY; CASTELLÀ, 2010; COSTA, 2012) were articulated, among others. From the results of the analysis, it was possible to verify that, of the items analyzed in this research, only a few promote critical reflections from the choice of the base text. The elaboration of Enem's Spanish items lacks an approach focused on criticality, through texts and themes that allow the questioning of imposed ideas, power relations and social practices present in society. Keywords: high school; Spanish; large-scale assessments.